First trimester placenta accreta: a rare clinical entity and diagnostic dilemma - Ng, Beng Kwang; Wang, PY; Ng, WYL; Mohammed F,; Lim, Pei Shan; Mahdy ZA, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
First trimester placenta accreta is a rare occurrence but potential life threatening and catastrophic. Most of these cases ended up with emergency hysterectomy. We report a case of incidental finding of placental accreta during evacuation of retained product of conception (ERPOC) for missed miscarriage. A 33-year-old, Gravida 4 Para 2 + 1 at 15 weeks’ gestation admitted for missed miscarriage, failed medical evacuation requiring ERPOC. There was excessive bleeding during the procedure and required hysterectomy and bilateral internal iliac artery ligation. Histopathological examination confirmed products of conception with evidence of placenta accreta. This case highlighted the diagnostic dilemma and importance of early accurate diagnosis of placental accreta prior to any surgical intervention for miscarriage.